LITERATURE OF REVIEW THE IMPACT OF SOCIAL MEDIA, LIFESTYLE AND DIGITAL PAYMENT APPLICATIONS ON CONSUMPTIVE BEHAVIOR OF BHAYANGKARA JAKARTA UNIVERSITY STUDENTS IN 2023 - Diah Ayu Sefianggraini (Draf Solusi Indonesia, 2023)
Consumptive behavior is excessive behavior regardingconsuming something. Social media, a technology knownas social media, is a digital platform that facilitates usersto communicate with each other in a much wider scope.Lifestyle is an achievement that a person has whichincludes its use in everyday life. The digital paymentapplication is a financial technology that makes it easierfor people to carry out all financial activities. This researchused a simple linear regression method on 89 samples.